Tacrolimus Protects Podocytes from Apoptosis via Downregulation of TRPC6 in Diabetic Nephropathy - Ruixia Ma; Ying Wang; Yan Xu; Rui Wang; Xianghua Wang; Ning Yu; Minghui Li; Yan Zhou (Journal of Diabetes Research)
Podocyte injury plays an important role in diabetic nephropathy (DN), and apoptosis is one of its mechanisms. The transient receptor potential channel 6 (TRPC6) is expressed in podocytes and mediates podocyte injury induced by high glucose levels. Tacrolimus is a novel immunosuppressive agent that is reported to play an important role in podocyte protection. The purpose of this study was to investigate the potential mechanism of podocyte protection by tacrolimus in a type 2 diabetic mellitus (T2DM) rat model and in immortalized mouse podocytes (MPC5). Transmission electron microcopy was used to evaluate renal injury morphology. After treatment with FK506, we measured 24-hour urinary albumin-to-creatinine ratios and creatinine clearance rates as well as major biochemical parameters such as glucose, insulin, serum creatinine, urea nitrogen, total cholesterol, triglycerides, alanine transaminase, and aspartate aminotransferase. Nephrin and TRPC6 protein expression and podocyte apoptotic rates in vivo and in vitro were measured using immunohistochemical staining, TUNEL assays, and flow cytometry, respectively. Western blot was used to measure expression of cleaved-caspase-3 and bax/bcl-2. Exposed to high glucose (HG), DM rats exhibited disrupted biochemical conditions and impaired podocyte structure. Decreased expression of nephrin and increased expression of TRPC6, cleaved-caspase-3, and bax/bcl-2 ratios were found in podocytes, along with higher apoptotic percentage, while tacrolimus intervention counteracted the effect of HG on podocytes. Our results suggest that tacrolimus protects podocytes during the progression of type 2 diabetic nephropathy, possibly ameliorating podocyte apoptosis by downregulating the expression of TRPC6.